2020
DOI: 10.1111/jhn.12809
|View full text |Cite
|
Sign up to set email alerts
|

Leptin gene polymorphism (rs 7799039;G2548A) is associated with changes in lipid profile during a partial meal‐replacement hypocaloric diet

Abstract: How to cite this article Primo D., Izaola O. & de Luis D. (2021) Leptin gene polymorphism (rs 7799039;G2548A) is associated with changes in lipid profile during a partial meal-replacement hypocaloric diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…A limitation in this context is that only serum leptin concentrations had been measured. Genetic information might have offered further insight since it had been shown that polymorphisms of the leptin receptor gene are able to inhibit the decrease of serum leptin levels during dietary intervention [39] and are associated with blood lipids [40]. Therefore, we could just speculate about potential mechanisms, especially in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation in this context is that only serum leptin concentrations had been measured. Genetic information might have offered further insight since it had been shown that polymorphisms of the leptin receptor gene are able to inhibit the decrease of serum leptin levels during dietary intervention [39] and are associated with blood lipids [40]. Therefore, we could just speculate about potential mechanisms, especially in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Gene polymorphism is demonstrated to be associated with the biomedical functions of MR. Leptin gene polymorphism (rs 7799039; G2548A) and RS9939609 FTO gene variant are associated with weight loss, insulin resistance, and lipid profile alterations after a low-calorie MR diet [75][76] . ACYL-CoA synthetase long-chain 5 polymorphism also correlates with weight loss and metabolic benefits in response to a low-calorie MR diet [77] .…”
Section: Other Mechanismsmentioning
confidence: 99%